Autoimmune glomerulonephritis in a multiple sclerosis patient after cladribine treatment. (October 2021) - Schönfelder, Kristina; Schuh, Helene; Pfister, Frederick; Krämer, Julia; Eisenberger, Ute; Skuljec, Jelena; Hackert, Jana; Ruck, Tobias; Pfeuffer, Steffen; Fleischer, Michael; Gäckler, Anja; Hagenacker, Tim; et al.
Background: Oral cladribine is an approved disease-modifying drug for the treatment of relapsing multiple sclerosis. In controlled clinical trials as well as in post marketing safety assessments, autoimmune conditions have not yet been reported as a specific side effect of cladribine. Objective and Results: Here, we report a case of anti-glomerular basement membrane antibody-mediated glomerulonephritis that occurred shortly after the fourth cladribine treatment cycle. Conclusion: Neurologists should be attentive to the development of secondary autoimmunity in cladribine-treated patients.